EFFICACY OF TERIPARATIDE IN COMMINUTED FRACTURE HEALING IN LOWER LIMB: A RETROSPECTIVE STUDY - DUDHIA, SNEH; MAHAJAN, KETAS (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study was to show the efficacy of teriparatide in comminuted fracture healing and improvement in overall functional recovery. Methods: A total of 30 subjects who suffered from comminuted fractures of lower limb were selected. Subjects were categorized into two groups: Group A (n=15) contained individuals with teriparatide administration and Group B (n=15) contained individuals who were not administered teriparatide. 20 mg of teriparatide was injected subcutaneously for a period of 3 months. Patients were followed up ay durations of 4, 8, and 12 weeks. Obtained data were entered into Microsoft Excel Worksheets and descriptive analysis was performed. Chi-square test was used to analyze all obtained data. Results: Among Group A patients, the fracture healing rates were found to be significantly earlier with comparison to control group (Group B). Conclusion: Teriparatide was observed to be effective in comminuted fracture healing and has demonstrated good clinical outcome.